Role Of The International Book Fair To Supply Books For Libraries Of Tehran & Shahid Beheshti University Of Medical Science - Fereidun Azadeh; Shanaz Nori Sandyani; Seyed Javad Ghazimirsaeed (Tehran University of Medical Sciences, 2012)
Background and Aim: The international book fair is an opportunity for school libraries. This study was conducted to determine the role of the Tehran international book fair to provide books for school libraries. Materials and Methods: The study is a descriptive survey. Employees and authorities worked in libraries affiliated to Tehran and Beheshti Medical Sciences Universities consisted the study population. Sample size included 41 individuals(26 staff and 15 officials). For data analysis descriptive statistics by using one sample t- test, chi square, ANOVA and correlation were used. Results: The highest average score dedicated to choose books in school libraries was a scale of a 3/35± 0/89. With an average score of 3/06±0/07, the role of International book fair in supplying books for school libraries was moderate. Correlation test showed that problems of school libraries had the highest correlation(r=0/36) while the lowest correlation was related to the possibility of book supply(r =0/067). Conclusion: The international book fair does not have an effective role in supplying books for school libraries. It is necessary to use new approaches to supply books for academic libraries.